Serum Prolactin Level in Children with Febrile Seizure and Epileptic Seizure; Comparative Study - Mahendrappa, Kotyal B.; Sathya, S. Perumal; Suma, M.N. (Journal of Nepal Paediatric Society, 2017)
Introduction: Transient hyperprolactinaemia has been reported to follow unprovoked seizures, a finding proposed to be useful in the differential diagnosis of epilepsy. On this basis we conducted a study with an objective to compare the postictal serum prolactin level in children with febrile seizures (FS) and epileptic seizures (ES) to evaluate, whether serum prolactin (PL) could be used a predictor in the diagnosis of ES. Material and Methods: This was a prospective comparative study was conducted on 52 children (26 in febrile seizures group and 26 in epileptic seizure group) in the age group of six months to five years. Children with CNS infection, developmental delay, structural CNS defects or neurological abnormality, metabolic disorders and those on drugs, known to have altered serum prolactin level were excluded. Blood for estimation of serum prolactin was collected within 180 minutes of occurrence of seizure. Level of serum prolactin was quantitatively assayed by chemiluminescence method and the levels were considered high, if values were greater than 23 ng/ml, which is the upper limit of normal for all age groups and both sex. Results: The mean serum prolactin level in epileptic seizures group was 25 ng/ml and that of febrile seizures group was 10.72 ng/ml. High level of serum prolactin was noted in 17 children (77.2%) with GTCS and 3 children (75%) with CPS. None of the children with febrile seizures had significant raise in the level of serum prolactin. Conclusion: There is a significant rise in serum prolactin level in children with epileptic seizures compared to febrile seizures, if measured within 3 hours of occurrence of seizures. Thus, the post-ictal serum prolactin level can be used as an additional investigation to diagnose or predict epileptic seizures in children.